Yoga and the Hindu Tradition - J B C (Journal of Dharma, 1976)
In recent times Yoga has gained an extraordinary popularity in the West. New books on "how to meditate", or "how to relax" appealing to Yoga techniques are making their appearance almost every day in the bookstores. But in spite of their reference to ancient Indian systems and the Yogis and Maharishis of India, what is laddled out in them are merely physical exercises or psychic practices with a good mixture of techniques drawn from psychiatry and counselling, with very little reference to the metaphysical and religious view point on which Yoga was based. This distortion is abetted and encouraged by the numerous Western style, expensive yoga centres even in India, where with all the ceremony and ritual of guru worship people can come nowhere near authentic yoga. In this book under review, published first in French in 1973 Jeanne Varenne protests against this dishonesty and tries to present to the general reader the correct perspective.